2020
DOI: 10.21512/bbr.v11i1.6028
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Environmental Management Accounting on Corporate Sustainability

Abstract: This research aimed to examine the effect of Environmental Management Accounting (EMA) on corporate sustainability in mining, agriculture, construction and construction materials, energy, textile and apparel companies in Indonesia from 2014-2018. This research had 87 observations from 20 in Indonesia from 2014-2018. EMA was measured by eco-efficiency energy. Meanwhile, corporate sustainability was measured by environmental and social factors. The researchers used content analysis to measure entity sustainabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 12 publications
0
15
0
2
Order By: Relevance
“…He opined that effective EMA practices lead to improved organizational performance. In addition, some empirical studies such as by Christine et al (2019) and Pratiwi et al (2020)have established a positive relationship between EMA practices and financial performance. This is because the benefits of EMA practices offset the cost (Tung et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…He opined that effective EMA practices lead to improved organizational performance. In addition, some empirical studies such as by Christine et al (2019) and Pratiwi et al (2020)have established a positive relationship between EMA practices and financial performance. This is because the benefits of EMA practices offset the cost (Tung et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…There are some approaches for a business to create value which is through the adoption of EMAS. Pratiwi, Meutia, and Syamsurijal (2020) revealed that EMAS adoption has a significant positive relationship with corporate sustainability. Value creation within the current study is considered value-added by enhancing financial performance, market performance, and environmental performance.…”
Section: Value Creationmentioning
confidence: 99%
“…A study done by Larojan and Thevaruban (2014) found that EMAS application correlates positively with the financial performance of the listed manufacturing companies in Sri Lanka. Prior researchers found that implementing environmental practices positively improves financial performance (Pratiwi, Meutia & Syamsurijal, 2020;Ong, Teh, Ng & Soh, 2016). Firms certainly spend much money when adopting EMAS in their organizations.…”
Section: Emas Adoption and Value Creationmentioning
confidence: 99%
“…Rahman, Meero, dan Mansur (2020) mengemukakan bahwa EMA memiliki dampak signifikan terhadap keunggulan kompetitif (keunggulan pemimpin biaya, keunggulan diferensiasi berkelanjutan, dan keunggulan segmentasi pasar berkelanjutan). Pratiwi et al (2020) juga mengemukakan bahwa penerapan EMA membuat perusahaan memperoleh keunggulan kompetitif, yang nantinya akan meningkatkan nilai perusahaan sehingga EMA berpengaruh positif dengan keunggulan kompetitif (competitive advantage).…”
Section: Pendahuluanunclassified
“…Hal ini sesuai dengan hipotesis yang menyatakan bahwa EMA berpengaruh positif dengan keunggulan kompetitif (competitive advantage). Hal tersebut sejalan dengan penelitian Dunk (2007), Rahman et al (2020), dan Pratiwi et al (2020) yang menyatakan jika ada pengaruh positif antara EMA dengan keunggulan kompetitif. EMA memberikan dampak terhadap peningkatan keunggulan kompetitif (keunggulan pemimpin biaya, keunggulan diferensiasi berkelanjutan, dan keunggulan segmentasi pasar berkelanjutan ) dari perusahaan.…”
Section: Hasil Dan Pembahasanunclassified